Pharmacokinetic Study of Multiple Components of Gelsemium elegans in Goats by Ultra-Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry. Issue 4 (25th January 2020) - Cao, Jun-Jie; Yang, Kun; Huang, Chong-Yin; Li, Yu-Juan; Yu, Hui; Wu, Yong; Sun, Zhi-Liang; Liu, Zhao-Ying
Abstract: Gelsemium elegans ( G. elegans ) has been used in traditional Chinese medicine . This plant is highly toxic to humans, but can promote the growth of pigs and goats in the veterinary clinic. It is a very complex mixture containing tens or hundreds of different components. Therefore, multiple-component pharmacokinetic studies of G. elegans are a major challenge due to the lack of authentic standards of the components. The purpose of this study was to investigate the plasma pharmacokinetics of multiple components after a single oral dose of G. elegans in goat using a sensitive ultra-performance liquid chromatography coupled to tandem mass spectrometry method for the simultaneous semiquantification of multiple alkaloids without standards. The method was validated in terms of the specificity, LOD, LOQ, linearity, accuracy, precision and matrix effects. To validate the global pharmacokinetic characteristics, the results obtained from the semiquantitative analysis of three authentic compounds (gelsemine, koumine and humantenmine) were compared with the absolute quantification from our recently published method. The results showed that the two methods had similar analytical results, and the obtained values of T max, T 1/2 and MRT0−t of the three alkaloids were similar between the two methods. In addition, the values of C max and AUC0−t of the three alkaloids after normalization were close to the real values, which indicated that this semiquantitative method could be used in the pharmacokinetic study of multiplecomponents. Then the pharmacokinetic parameters of 23 other G. elegans alkaloids in goats were obtained. The results suggested that the gelsedine-type alkaloids were the major active ingredients that predict and explain the efficacy and toxicity of G. elegans.